2021
DOI: 10.32920/ryerson.14665932.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative life cycle assessment: ground source heat pump system versus gas furnace and air conditioner system

Abstract: Ground source heat pump (GSHP) systems are an extremely efficient space heating and cooling technology. There is a large consensus throughout the literature that GSHP systems can reduce operational CO2 emissions by up to 80% in comparison to natural gas furnace (GF) and air conditioner (AC) systems. The literature is limited; however, in regards to the specific environmental impacts associated with the systems, as well as the impacts that occur throughout the systems’ entire life cycle. In this project, a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…An LCA often requires many assumptions due to the lack of data and information in different regions and industries. Many studies have investigated the LCA of GSHP systems and compared them to conventional HVAC systems for various regions, including hot, cold, and mild [23][24][25][26][27][28][29][30]. Smith et al [29] investigated the LCA of a GSHP system in a typical home in New Jersey and concluded that the primary environmental impact is the required energy to operate the system over its assumed 25-year life cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An LCA often requires many assumptions due to the lack of data and information in different regions and industries. Many studies have investigated the LCA of GSHP systems and compared them to conventional HVAC systems for various regions, including hot, cold, and mild [23][24][25][26][27][28][29][30]. Smith et al [29] investigated the LCA of a GSHP system in a typical home in New Jersey and concluded that the primary environmental impact is the required energy to operate the system over its assumed 25-year life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Hunter [23] showed that GSHP systems benefit from higher energy efficiency, reflecting on the life cycle's operation stage with lower environmental impacts compared to natural gas and air conditioner systems. Based on their results, assuming installation in Toronto and using Ontario's energy grid, the GSHP system is a better option by considering just the operation stage.…”
Section: Introductionmentioning
confidence: 99%